ASAS IKHITYATI PADA AKAD PEMBIAYAAN MUDHARABAH DI LINGKUNGAN PERBANKAN SYARIAH - Trisadini Prasastinah Usanti; Prawitra Thalib (Universitas Airlangga, 2016)
Agreement in Arabic termed Mu'ahadah Ittfa, or Contract. In the language of Indonesia known by contract, agreement or approval meaning is an act where one or more bind itself against someone else or more. Equivalent of the word Agreement in Arabic is aqad. In terms of jurisprudence in general contract means something into someone's determination to carry out, both emerging from one party such as endowments, divorce, and the oath, as well as emerging from the two parties such as sale and purchase, rent, wakalah and pawn. On the basis of Islamic banking environment there are ikhiyati where this principle should be applied on the mudharabah financing contract. Basic Ikhtiyati/prudence had the meaning that each contract is done with careful consideration and implemented appropriately and carefully. The implementation of the principle of mudharabah financing contract on ikhtiyati requires the analysis of pembiyaan before the financing approved by the syariah bank, if the customer (mudharib) violate these restrictions, then the mudharib should be responsible in case of loss.